Sacadura Cabral and the Dawn of Portuguese Aviation - Neves, Fernando M. S. P. (2022)
Sacadura Cabral was one of the two Portuguese navigators that crossed by air the South Atlantic in the beginning of the 20th century. From 1901 to 1915 Sacadura was at Mozambique and Angola where he developed geodetic and geographical missions of the greatest importance for Portuguese interest at Africa. With the Great World War requirements as a Navy Officer with 34 years old he decided to serve Portugal at the Aviation. In 1915 he went to France and obtained its pilot license. In 1916 Sacadura returned to Portugal and begun its instructor pilot career. He developed the “path corrector” which he created to compensate the drift caused by wind. In 1922 Sacadura made the First Air cross from Europe to South Atlantic. In 1923 he proposes himself to make an attempt to the First Air Circumnavigation Journey. He developed all its possible efforts to initiate this journey in March of 1924; however some delays had forced him to postpone the journey. Sacadura received important official medals and prizes, including the PhD Honoris Causa from the Universities of Lisbon and Oporto. In 1924 he died before he could carry out its Circumnavigation Air Journey.